Electrical Insulation in a 400 V Battery Module for Hybrid Vehicles - Memari, Mohammad Hassan; Nakanwagi, Victoria (My University, 2014)
The growing interest in the use of electric vehicles worldwide has resulted in awareness of the importance of ensuring the safety of these vehicles for users. The safety of electric vehicles is greatly determined by the state of the insulation between the high voltage system and the ground. In this thesis, the behaviour of the insulation in a high voltage traction battery used in a hybrid vehicle has been studied and evaluated under different operational conditions. The objective of this thesis was to assess how much the insulation resistance of the battery system is affected by the battery geometry and its environment of operation. The international standards applicable to insulation in electric vehicles have been studied to determine the requirements that the battery insulation system must adhere to and to determine which tests are recommended for testing the battery insulation system. In this work the results from the insulation resistance tests, partial discharge tests and environmental tests performed on a battery system are presented. The results from insulation resistance tests combined with environmental tests under varying temperature and humidity conditions show that the presence of moisture on the insulating surfaces of the battery greatly decreases the insulation resistance of the battery. The partial discharge tests show that grounding of the conducting non-current carrying parts of the battery through a path of low resistance is important to minimize discharges. At operational voltages, the weakest areas of the battery system insulation have been located inside the battery module on the edges of the cells.
Keywords: Energi; Elkraftteknik; Hållbar utveckling; Transport; Energy; Electric power engineering; Sustainable Development; Transport